Finite element analysis on flush end plate connection using LUSAS software - Mohd. Yusoff, Che Som (2006)
This paper present and discuss the finite element method as an alternative method to investigate the behaviour of the flush end plate. The finite element results are compared with the results of the experimental tests taken from literature. The three dimensional materially static non-linear finite element analys is using LUSAS modeller was perform the bolted flush end plate connection. The moment-rotation curve was plotted from the result and the curve was superimpose with the experimental curve to check the accuracy of the analyses method. It was found that the two curves coin-side quite well with each other. The difference in values of the moment resistance of the two curves is 15..62 %. In this research also found that a 3.125% increase in the end plate thickness produces a 3.03% the moment of resistance of the connection. The results of this study shows an agreement with previous researchers that the connecti behaves in between pinned and fully rigid and posses some rotational stiffness